Automated inspection of textured ceramic tiles - Smith, Melvyn L; Stamp, Richard J (Computers in industry, 2000)
An innovative object-centred approach for the visual inspection of textured ceramic tiles has been developed for the acquisition of product quality control data. A demonstrator system has been constructed for the analysis of complex surfaces, surfaces which possess detailed three-dimensional topographic features, which are concealed by coincident regular or random chromatic patterns. The technique is able to isolate mixed topographic and chromatic surface features in order to allow for subsequent separate analysis. Surface topography is captured as an array of perturbed surface normals, known as a surface bump map, while the surface reflectance is isolated as a separate albedo image. Synthetically rendered images of the bump map description allow surface topography to be viewed off-line under user defined virtual illumination conditions, and in isolation from the surface albedo. Topographic features defined by the bump map description may be subject to analysis in terms of perturbation thresholding, or integrated to recover their three-dimensional relief. The technique has application for the quality inspection of a wide range of manufactured and processed surfaces, uses a low-cost fixed lighting configuration, requires no initial training, is largely pose invariant, and has been tested on a representative range of real tile samples. Experimental results are presented in the paper.